Collaborative Pattern and Authorship Trends in Library Herald Journal: A Bibliometric Study (LIS TODAY, 2026)
This paper is an analysis of the journal Library Herald’s contribution to library science  from 2015 to 2024. A total of 338 articles were included in this study. The research will  focus on drawing out the trends, major areas of research, and the influence of the journal  on the development of research in the library science field. Using specific terms and  methods, we assessed the number of publications, authorship, authorship partnerships,  article publication by year, and paper classification by professional category, which are  covered by this study. The analysis demonstrates that the journal is gaining more and  more recognition and is one of those participating in the spread of research findings  of critical value. This review identifies the journal Library Herald as one of the most  important channels in enhancing the quality and standards of teaching and research,  and it provides an understanding of its contribution and the future formulation of  research in this rapidly developing field. This abstract provides a brief background of the  study, its methodology, major findings, and how the journal Library Herald is relevant  to research productivity.
Keywords: Publication Analysis; Research Collaboration; Bibliometric Analysis; Authorship Pattern; Library Herald; Scientometric